graal: a Drosophila gene coding for several mosaic serine proteases - Munier, Anne Isabelle; Medzhitov, Ruslan; Janeway, Charles A.; Doucet, Daniel; Capovilla, Maria; Lagueux, Marie (Insect biochemistry and molecular biology, 2004)
Serine proteases play vital roles in several biological processes such as development and immunity. We have characterized Graal, a large multi-domain serine protease from Drosophila. Graal is spliced in at least three transcripts that are present throughout development. The domains found in Graal proteins are: chitin-binding domains (CBD), scavenger receptor cysteine-rich (SRCR) domains, low density lipoprotein receptor cysteine-rich (LDLR-CR) domains, histidine and proline-rich domains, a NGGYQPP-repeat domain and a serine protease domain. The last 2370 nucleotides of these RNAs are identical and encode a His-rich domain, two SRCR domains, two LDLR-CR domains and a protease domain. The transcription of graal is upregulated after fungal or bacterial infection. Analysis of the Iso1 ( y;cn,sp,bw) strain shows that graal transcription is impaired in this fly line due to the insertion of a retrotransposon in the sixth exon. However, no phenotype could be observed consecutive to the absence of graal full length transcripts, particularly in the context of an immune challenge.